Penentuan Susu Formula Ideal untuk Bayi Menggunakan AHP di Wilayah Kota Mataram - Switrayni, Ni Wayan; Aini, Qurratul; Irwansyah, , (Jurnal Matematika; Vol 6 No 2 (2016)DO - 10.24843/JMAT.2016.v06.i02.p73, 2016)
This research aims to determine the ideal formula milk for infants aged 1-3 years in the Region of Mataram City of West Nusa Tenggara. Method of this research is inductive. This research used Analytical Hierarchy Process (AHP) to determine the ideal formula milk for infants aged 1-3 in Mataram City Region of  West Nusa Tenggara based on several criteria such as price, nutritional value, net of packaging, and flavors. The result of this research showed that Analytical Hierarchy Process (AHP) can be used as one of the methods of decision-making in determining the ideal formula milk for infants aged 1-3 in Mataram City Region based on the four criteria.
Keywords: Analytical Hierarchy Process (AHP), formula milk, Mataram City Region